Opening the Black Box: Internal Capital Markets and Managerial Power - GLASER, MARKUS; LOPEZ‐DE‐SILANES, FLORENCIO; SAUTNER, ZACHARIAS (Journal of Finance, 2013)
ABSTRACT We analyze the internal capital markets of a multinational conglomerate, using a unique panel data set of planned and actual allocations to business units and a survey of unit CEOs. Following cash windfalls, more powerful managers obtain larger allocations and increase investment substantially more than their less connected peers. We identify cash windfalls as a source of misallocation of capital, as more powerful managers overinvest and their units exhibit lower ex post performance and productivity. These findings contribute to our understanding of frictions in resource allocation within firms and point to an important channel through which power may lead to inefficiencies.